Epidermoid Cyst Arising in the Buccal Mucosa: Case Report and Literature Review - Fábio Wildson Gurgel Costa; Francisco Samuel Rodrigues Carvalho; Filipe Nobre Chaves; Stephanie de Almeida; Ana Paula Negreiros Nunes Alves; Régia Maria do Socorro Vidal Patrocinio; Fabrício Bitu Sousa; Karuza Maria Alves Pereira (University of Zagreb. School of Dental Medicine, 2015)
Epidermoid cysts are benign subcutaneous lesions, and the large majority of these cysts affect the floor of the mouth; however, the buccal mucosa is not a usual site of occurrence. To date, only 5 articles have been published with 6 cases of epidermoid cysts arising in the buccal mucosa. Therefore, the aim of this study was to describe the clinical, histopathological and immunohistochemical features of a case of epidermoid cyst located in the buccal mucosa. To our knowledge, this is the first report of an oral epidermoid cyst describing an intense foreign body gigantocellular inflammatory reaction against epithelial keratin component. Although the usual diagnosis for epidermoid cysts is based on histopathological findings, this case report addresses novel information regarding to the immunohistochemical pattern that may be found in these lesions.